Primary healthcare practice learning environment: A description of students' perspectives - Soyi Joyce Mosia; Annemarie Joubert (Elsevier, 2020)
Primary healthcare practice environments provide opportunities for nursing students to master clinical skills and to acquire professional competencies. To enhance clinical learning, this environment must support students' learning needs. The study aimed to describe the primary healthcare practice learning environment from students' perspective, to determine if this environment supported their learning needs. A quantitative, descriptive, cross-sectional design was followed. The population was 160 third-year students who had completed their second-year clinical practice. The students were registered at three campuses of a Free State school of nursing. 146 students agreed to complete the structured, self-administered questionnaire. The results were as follows: The mean cumulative percentage calculated indicates that students were mostly supported before clinical placement (89.6%), at the commencement of clinical placement (85.4%), and during clinical placement (75.6%). The cumulative percentages (84.9%) for strongly agree/agree showed that services rendered at primary healthcare practice learning environments were adequate. The Chi Square and Fischer Exact tests were used to compare scores and to determine the distributions of categorical data. Considering only those statements with a p-value < 0.05, differences were found between the three campuses. Mean values related to 18 statements seem to indicate that the practice learning environment of Campus C enhanced students' clinical learning (72.2%) better than that of Campus A (47.3%) or B (47.66%). A limitation of this study is that it included one nursing programme, which may limit the relevance of its findings to a specific nursing programme.